Narrativas educativas de professoras que atuam na EJA: percepções sobre gênero e sexualidade - Santos, Luiz Fábio (Universidade Federal de São Carlos, 2016)
This paper reports a research linked to the Center for Studies and Research on Narratives, Training and Teaching Work (Nepen) developed at the Graduate Program in Education of the Federal University of São Carlos (UFSCar) - Campus Sorocaba. The research is focused on perceptions about gender and sexuality to teachers who work in the Youth and Adult Education (EJA). The issue that guides the development of this research of the following question: What are the perceptions about gender and sexuality evidenced in educational narratives produced by teachers who work in adult education and from them which settings can guide their educational practices? The research aims to seek to understand the perceptions of gender and sexuality to teachers who work in adult education and the importance of discussing these issues in the statement of respect for differences in school; point out problems for convergence between education and issues related to gender and sexuality in the adult education and discuss the perceptions of gender and sexuality in the relationship of the daily school EJA driving the reflection on the values that mark our society. To answer this problem the study is structured from a qualitative perspective and uses for production data preparation of educational narratives in the context of an extension course offered for education professionals working in adult education. As a methodological theoretical framework considered the contributions of Freire (1976,1996,1988); Valdés (2014) and Vóvio (2013) for the reasoning of EJA; Louro (1997, 2000, 2009, 2011) and Miskolci (2010, 2015) for reasons of gender and sexuality; Bogdan and Biklen (1994), Deslauriers and Kérisit (2012), Thiollent (2011), Tripp (2005); Sicardi Nakayama (2015), Bardin (1977) and Franco (2005), for reasons of methodological route and analyze data. For teacher training: Sicardi (2008), Cunha (1998) and Nóvoa (2009). The results foresee possible educational subsidies for improving the social quality of education in classrooms of AYE.
Narratives education of teachers working in Youth and Adult Education: perceptions of gender and sexuality
Keywords: Gênero; Sexualidade; Educação de Jovens e Adultos; Narrativas Educativas; Formação Docente; Gender; Sexuality; Youth and Adult Education; Narratives Education; Teacher Training; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM